Lithium Batteries: Computational Design and Preparation of Cation‐Disordered Oxides for High‐Energy‐Density Li‐Ion Batteries (Adv. Energy Mater. 15/2016). Issue 15 (10th August 2016) - Urban, Alexander; Matts, Ian; Abdellahi, Aziz; Ceder, Gerbrand
Abstract : In article number 1600488, Gerbrand Ceder and co‐workers present a computational high‐throughput approach to identify novel disordered oxides for high‐capacity Li‐ion battery cathodes. The image shows the structures of ordered and cation‐disordered Li transition metal (TM) oxides. Various TM combinations, predicted to form either ordered or disordered phases are visualized as small and large circles, respectively.